Lacustrine faciès from canadon asfalto formation (callovian-oxfordian), las chacritas, cerro condor, chu-hut province - Cabaleri, N.G. (1999)
The lower section of Canadon Asfalto Formation (Callovian-Oxfordian) is located at Las Chacritas, Cerro Condor area, on the middle course of Chubut River. It is represented by lacustrine carbonate faciès with interbedded volcanic layers accumulated in the rift system of the Somuncura-Canadon Asfalto Basin. Eight microfacies (MF), defining the lake environments, and three biohermal faciès (MFB) corresponding to an extensive microbialitic belt overlying eulittoral sediments have been recognized: The microfacies are: MF1, mudstone with microbial lamination, related to supralittoral shallow ponds; MF2, biohermal intraclastic floatstone linked to storm episodes; culminating with evaporitic levels; MF3, mudstone with evidence of dessication formed in stagnant water; MF4, microbial-peloidal mudstone/wackestone with evidence of sporadic wave currents, in a eulittoral environment; MF5, intraclastic grainstone/rudstone with pedogenic alterations showing evidence of wave action in a eulittoral area; MF6, oncoidal floatstone interpreted as an hiperconcentrated flow; MF7: Bio-intra-siliciclastic packstone/wackestone accumulated in infralittoral conditions and MF8, silicified bulbous stromatolites related to the outlet of fluvial channels. The biohermal faciès are: MFB9, mudstone with stromatolites and wackestone levels; MFB10, planar stromatolites and MFB11, hemispherical stromatolites with chalk crust. Behind the biohermal belt, palustrine limestones locally show layers with episodic storm floods. The microfacial and facial distribution represents expansion and contraction cycles of a closed lake, controlled mainly by the precipitations. ©1999 Asociacián Gcológica Argentina.